2022
DOI: 10.1039/d1cc06086d
|View full text |Cite
|
Sign up to set email alerts
|

Janus bifunctional periodic mesoporous organosilica

Abstract: A novel protocol for the synthesis of a Janus periodic mesoporous organosilica material (JPMO) is presented here. In this strategy, the surface of the hollow silica material was selectively functionalized...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 52 publications
0
13
0
5
Order By: Relevance
“…Recently, we reported the one-pot synthesis of a Janus bifunctional PMO with a highly anisotropic structure and the ability to form a stable a Pickering emulsion. [75] Another challenge is the lack of a general procedure for the synthesis of Janus materials with "absolute selectivity" while keeping a precise surface functionality. Some procedures suffer from multiple steps (that may reduce the final yield of the material and increase costs), some timeconsuming procedures, and the employment of polymeric templates, which in industrial-scale synthesis are not costeffective.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we reported the one-pot synthesis of a Janus bifunctional PMO with a highly anisotropic structure and the ability to form a stable a Pickering emulsion. [75] Another challenge is the lack of a general procedure for the synthesis of Janus materials with "absolute selectivity" while keeping a precise surface functionality. Some procedures suffer from multiple steps (that may reduce the final yield of the material and increase costs), some timeconsuming procedures, and the employment of polymeric templates, which in industrial-scale synthesis are not costeffective.…”
Section: Discussionmentioning
confidence: 99%
“…In our recent study on the application of Janus catalysts, we synthesized a Janus material bearing a single-site palladium complex on one face of hydrophobic silica nanosheets (Figure 12a). [48] The activity of this catalyst was tested in a Wacker-type oxidation of styrene with H 2 O 2 to generate acetophenone (Figure 12b). The results indicated that acetophenone was obtained in 88 % yield after only 60 min at 80 °C by employing 1 mol % of the catalyst (based on palladium) in a mixture of acetic acid and water.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Daher ist die Entwicklung hochleistungsfähiger katalytischer Systeme, die Oxidationsreaktionen in wässriger Phase mit kurzen Reaktionszeiten ermöglichen, ein wichtiger Punkt für die Verringerung der Zersetzung von H 2 O 2 . In unserer jüngsten Studie für die Anwendung von Janus‐Katalysatoren haben wir ein Janus‐Material synthetisiert, das auf einer Seite von hydrophoben Siliciumdioxid‐Nanosheets einen Single‐Site‐Palladium‐Komplex trägt (Abbildung 12a) [48] . Die Aktivität dieses Katalysators für die Erzeugung von Acetophenon wurde anhand der Wacker‐Oxidation von Styrol mit H 2 O 2 untersucht (Abbildung 12b).…”
Section: Anwendungen In Der Katalyseunclassified
“…b) Die Wacker-Oxidation von Styrol zu Acetophenon in Gegenwart von 1 mol-% des Janus-Katalysators bzw. von PdCl 2 [48]. Abbildung 13. a) Immobilisierung von Palladium-Nanopartikeln an der Oberfläche einer modifizierten Janus-Zellulose.…”
unclassified